Development of Retroviral Vectors for Tissue-Restricted Expression in Chicken Embryonic Gonads - Lambeth, Luke S.; Ohnesorg, Thomas; Cummins, David M.; Sinclair, Andrew H.; Smith, Craig A. (PLOS ONE, 2014)
The chicken embryo has long been a useful model organism for studying development, including sex determination and gonadal differentiation. However, manipulating gene expression specifically in the embryonic avian gonad has been difficult. The viral vector RCASBP can be readily used for embryo-wide transgene expression; however global mis-expression using this method can cause deleterious off-target effects and embryo-lethality. In an attempt to develop vectors for the over-expression of sequences in chicken embryonic urogenital tissues, the viral vector RCANBP was engineered to contain predicted promoter sequences of gonadal-expressed genes. Several promoters were analysed and it was found that although the SF1 promoter produced a tissue-restricted expression pattern that was highest in the mesonephros and liver, it was also higher in the gonads compared to the rest of the body. The location of EGFP expression from the SF1 promoter overlapped with several key gonad-expressed sex development genes; however expression was generally low-level and was not seen in all gonadal cells. To further validate this sequence the key testis determinant DMRT1 was over-expressed in female embryos, which due to insufficient levels had no effect on gonad development. The female gene aromatase was then over-expressed in male embryos, which disrupted the testis pathway as demonstrated by a reduction in AMH protein. Taken together, although these data showed that the SF1 promoter can be used for functional studies in ovo, a stronger promoter sequence would likely be required for the functional analysis of gonad genes that require high-level expression.